Learning material design for teaching genetics while implementing flipped classroom - Anna Carolinne Ferreira Bissoli; Gustavo Antunes dos Santos; Sandro José Conde (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
This paper shows the process of research and design of learning materials for flipped classrooms, an active teaching method that intends to switch from the traditional acquisition of content in class and to the assignments' resolution at home. In order to choose the content to be addressed, we based our efforts on a research that indicated "Genetics" as a subject of difficult comprehension. With the use of digital platforms, some flashcards, quizzes, mind maps, video and a website were produced to create the materials and promote the flipped classroom values. It is intended to show that the flipped classroom is an applicable approach, placing students at the center of the learning process.